2020
DOI: 10.7759/cureus.10341
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Risk Factors and Prevention of Capsular Contracture Following Implant-Based Breast Reconstruction and Cosmetic Surgery: A Systematic Review

Abstract: Capsular contracture is one of the most common complications of implant-based breast reconstruction or augmentation surgery. Despite advanced molecular biology, the exact mechanism of this complication is not fully understood. PubMed was searched for studies, published from 2015 to 2020, focused on potential risk factors and preventions of capsular contracture (CC) in patients who underwent implant-based breast surgery. A total of 533 articles were identified from PubMed, and 13 articles were selected ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Acellular dermal matrix, leukotriene (LTE) inhibitors, surgical procedures, antibiotic prophylaxis or irrigation, and other interventions all helped to lower the incidence of CC. 20 …”
Section: Resultsmentioning
confidence: 99%
“…Acellular dermal matrix, leukotriene (LTE) inhibitors, surgical procedures, antibiotic prophylaxis or irrigation, and other interventions all helped to lower the incidence of CC. 20 …”
Section: Resultsmentioning
confidence: 99%
“…This may be in line with many other studies that have demonstrated a positive correlation between the degree of capsular contracture and age or time after irradiation. 29 30 Older patients seem to have more severe capsular contracture than younger patients, and radiotherapy-induced capsular contracture tends to aggravate over time owing to radiation-induced irreversibility. Therefore, appropriate surgical intervention is critical for patients with more progressive fibrotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Capsular contracture in implant-based breast reconstruction can be a significant complication, sometimes necessitating an additional surgical procedure 36 . However, the current clinical evidence shows that the use of ADM can effectively reduce the incidence of capsular contracture 37 .…”
Section: Discussionmentioning
confidence: 99%